PSYCHOANALYSIS, MORALITY, AND IDEOLOGY PERSPECTIVES IN QUENTIN TARANTINO’S PULP FICTION MOVIE - Yoshua Veron Handika Putra Siadari; Nasywa Nuzula Ramadhani; Anicleta Yuliastuti; Ni Nyoman Sarmi; Rommel Utungga Pasopati; Dimas Eko Saputro (LPPM Universitas PGRI Adi Buana, 2025)
This article examines the complex relationships by understanding the perspectives of ideology, morality, and psychoanalysis. The main characters of this movie are Vincent Vega and Jules Winnfield. Pulp Fiction was directed by Quentin Tarantino in 1994. The authors of this article employ a qualitative method, which allows the reader to learn more about the object's background. The study demonstrates how these three viewpoints influence the characters' actions and the plot by looking at the psychological motivations, ethical issues and ideological factors at play in the movie. A deeper understanding of how Pulp Fiction deals with issues of identity management, ethical standards, and society's impact is made possible by the examination of these perspectives. The film offers an interesting story that challenges audiences to consider human nature and the idea of redemption in a morally unstable society. In conclusion, this movie is full of various literary devices and meanings, making it important to be underlined within psychoanalysis, morality and even ideology perspectives.